Surgical Management of Eloquent Supratentorial Low-Grade Gliomas with Special Emphasis on Intraoperative Imaging - Jakola, Asgeir Store; Senft, Christian; Unsgaard, Geirmund; Solheim, Ole (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Objective Eloquent diffuse low-grade gliomas (LGGs) threaten patients' neurologic function and are also associated with inferior survival. Many neurosurgeons still refrain from early resection due to the fear of iatrogenic neurologic injury. However, the perceived safety of expectant management strategies may soon be overshadowed by the progressive deficits of tumor growth in eloquent regions. It is also known that radical and successful surgery prolongs progression-free survival, overall survival, and may reduce seizure burden and also potentially neurocognitive functions. Thus early successful surgery with preservation of function has a significant impact on patients' health. In modern neurosurgery, safe resection is often possible with detailed knowledge of anatomy and function together with the active use of various intraoperative surgical tools. We present illustrative cases of eloquent LGGs treated with different intraoperative tools.Methods An introduction to important intraoperative tools in LGG surgery is provided by experts in the field and described in five cases viewed in the context of the recent LGG literature.Results We present five cases with presumed eloquently located LGGs where extensive resection was offered using different intraoperative techniques. The clinical and radiologic outcomes are described.Conclusions Correct use of intraoperative tools together with the surgeon's knowledge of anatomy and function will provide good functional and oncologic results in eloquently located LGGs. Watchful waiting or deferral of surgery due to tumor location (i.e., claiming inoperability) is very rarely good practice.
Keywords: glioma; magnetic resonance imaging; ultrasound; technology